Enhancing Students’ Motivation and Interest in Physics Learning Through PhET Interactive Simulations: A Systematic Literature Review - Nurul Istikoma (Indonesian Journal of Innovation and Educational Technology, 2026)
This study aims to examine the effectiveness of PhET Interactive Simulations in enhancing students’ motivation and interest in physics learning through a systematic literature review of scientific articles published between 2016 and 2025. The study is motivated by the low level of students’ motivation and interest in learning abstract physics concepts, which require interactive and engaging learning media. The method employed is a systematic literature review involving the systematic identification, selection, and analysis of 20 peer-reviewed scientific articles from national and international journals. The review focuses on the impact of PhET on students’ motivation, student interest, engagement, and independent learning. The findings reveal that PhET Interactive Simulations significantly improve students’ motivation and interest through interactive visualizations, high interactivity, and game-like simulation features, creating enjoyable and meaningful learning experiences. Furthermore, the accessibility of PhET contributes to increased independent learning frequency outside the classroom. In conclusion, PhET Interactive Simulations is an effective and innovative learning medium for enhancing students’ motivation and interest in physics learning and is recommended for integration into technology-based education in the digital era.